SISTEM PEMINJAMAN BARANG DAN PERALATAN LABORATORIUM SMK BERBASIS WEB - Laode Muh ZulFardin Syah; Muh. Ichsan Ali; Riana T. Mangesa; Darlan Sidik; Abdul Muis Mappalotteng (UNM Journal of Technology and Vocational, 2022)
This study aims to: (1) produce a web-based system for borrowing goods and laboratory equipment for Vocational High Schools, (2) Determine the level of feasibility of the system for borrowing goods and equipment in the web-based SMK Negeri 1 Papalang laboratory, (3) Find out user responses about the lending system. goods and equipment in the web-based laboratory of SMK Negeri 1 Papalang. The type of research used in this research is Research and Development (R&D) using the Rapid Application Development (RAD) development model. The subjects in this study were the Deputy Head of Facilities and Infrastructure, the head of competence, and teachers from SMK Negeri 1 Papalang, totaling 32 people. Data was collected through documentation and questionnaires. The data were analyzed using the ISO/IEC 9126 software testing method which includes aspects of functionality, portability, efficiency, reliability, maintainability, and usability. In the functionality aspect using test cases by two system experts, the portability aspect using various types of operating systems and web browsers, the efficiency aspect using GTMetrix for web page load testing, the reliability aspect using the WAPT application for system performance testing, maintainability aspects for maintenance testing and usability aspects. using a questionnaire. The result of this research is the development of a web-based system for borrowing goods and equipment in the laboratory of SMK Negeri 1 Papalang. The results of the system functionality test are considered good because X is close to 1, the portability aspect has no errors in various types of operating systems and web browsers, the efficiency aspect gets a page load time of 788ms with an average score based on 100% Performance, the reliability aspect gets 100% for durability, maintainability has met all three metrics and usability aspects are carried out by giving questionnaires to research subjects, the assessment given by research subjects gets a score of 84.5 in the "very good" category and is feasible to use. So it can be concluded that the level of feasibility of the software already meets the software quality criteria